2015
DOI: 10.1055/s-0034-1395585
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mTOR Pathway in Exercise-induced Cardiac Hypertrophy

Abstract: This study was designed to examine whether the mTOR signaling pathway would respond to long-term different intensity exercises and to observe the impact of exercise upon possible cardiac damage. Male Sprague Dawley rats were randomly divided into control group, moderate-intensity exercise group and high-intensity exercise group, and each exercise group had 4 observation time points (1-24 h). Exercise training lasted 8 weeks with a 2-day break for each week. Serum cTnI was measured by ELSIA and myocardium histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
1
22
2
Order By: Relevance
“…It is recently reported that mTOR is involved in high-fat diet-Induced cardiac hypertrophy in mice [ 9 ], and AKT/mTOR mediates programmed necrosis in neurons [ 26 ]. Thus, we hypothesized that mTOR signaling participated in PA-induced necroptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recently reported that mTOR is involved in high-fat diet-Induced cardiac hypertrophy in mice [ 9 ], and AKT/mTOR mediates programmed necrosis in neurons [ 26 ]. Thus, we hypothesized that mTOR signaling participated in PA-induced necroptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, mammalian target of rapamycin (mTOR), which is also essential for cardiomyocyte development, growth, and functions, regulates mitochondrial fatty acid utilization in the heart [ 8 ]. The AKT/mTOR signaling pathway has emerged as an important regulator in the pathogenesis of myocardial hypertrophy [ 9 ]. In cardiomyocytes, PI3K/mTOR/p70 (S6K) plays a critical role in the leptin-induced hypertrophy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise potentiates anabolic signaling (i.e., phosphorylation of Akt and mTOR) in the heart (17), which is a well-accepted mechanism that inhibits autophagy under starvation, but this creates paradox because exercise also promotes kinetophagy. Therefore, we explored the question of whether kinetophagy occurs in parallel with mTOR activation.…”
Section: Resultsmentioning
confidence: 99%
“…The exercise protocol was based on previous research and effective for the promotion of cardiovascular adaptation. 11,12) Inhibitor administration: When the first bout of exercise training had been executed, autophagy inhibitor 3methyladenine (3-MA, TEM group, 100 mg/kg on alternate days) and Compound C (TEC group, 100 μg/kg every day) were separately administered by i.p. injection for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%